Oncology-specific Qualified Clinical Data Registry (QCDR) measures to advance cancer care and achieve Merit-Based Incentive Payment System (MIPS) performance. Issue 28 (1st October 2022) - Crum, Erin; Adams, Taylor; Harrell, Robyn; Staggs, Stuart; Wilfong, Lalan S.
Abstract : 435 Background: Quality measurement is one of the four pillars of the Centers for Medicare and Medicaid (CMS) MIPS program. Few MIPS quality measures are specific to oncology. The US Oncology Network (USON) in collaboration with McKesson created a QCDR to align quality improvement reporting with oncology-specific measures to improve cancer care. Methods: The Practice Insights QCDR application was developed and submitted to CMS for approval in 2017. Integrated with an oncology-specific EHR (iKnowMed Generation 2), the QCDR leverages clinical content to automate calculation of quality measures. A multidisciplinary team was created to develop targeted oncology-specific measures that are clinically relevant, improve patient care, and reduce unnecessary healthcare costs. Results: The QCDR has been approved by CMS since 2017 allowing development of oncology-specific measures to monitor critical areas of cancer care. USON practices reported these measures as part of their MIPS participation. CMS established national MIPS program performance benchmarks for 4 measures due to measure feasibility, reporting ease, and high clinician adoption rates. PIMSH4 Pain Improvement (patient-reported outcome) was selected for public reporting through CMS Care Compare. CMS approved all 7 submitted QCDR measures for the 2022 MIPS program year. USON average performance (25 practices, representing 1, 787 clinicians) from 2019-2022 YTD demonstrates significant improvement ranging from 4%-10%. Conclusions: Creating an oncologic-specific QCDR allowed USON practices to report more meaningful quality measures through the MIPS program. QCDR measures provide insight for care teams and trends from 2019-2022 YTD demonstrate that USON practices achieved significant performance improvements in key areas of cancer care. Future development will refine and identify new measures that align with our patient care improvement activities to enable clinicians and care teams to focus on measures that matter.QCDR Measures Measure Type 2022 YTD USON Ave Performance 2022 CMS Benchmark 2019-2022 YTD % Improvement PIMSH1: Advance Care Planning in Metastatic Cancer Patients Patient Experience 35% 30% 10% PIMSH2: Utilization of GCSF in Metastatic Colorectal Cancer Cost/Resource Use 19% -- 8% PIMSH4: Patient-Reported Pain Improvement Patient-Reported Outcome 48% 43% 6% PIMSH8: Mutation testing for lung cancer completed prior to start of targeted therapy Process 55% -- 9% PIMSH9: Supportive Care Drug Utilization in Last 14 Days of Life Cost/Resource Use 8% 6% N/A* PIMSH10: Hepatitis B serology testing and prophylactic treatment prior to receiving anti-CD20 targeting drugs Process 58% 47% 4%** PIMSH12: COVID-19 Vaccinations Process 30% -- N/A*** * Measure changed; results not comparable ** Measure available beginning 2020 *** New measure in 2022 .